ANALISIS SISTEM PUSAT KEWILAYAHAN KABUPATEN LAMPUNG SELATAN - Kurnianingsih, Nela Agustin; Agustine, Verlina; Winata, Lestari P. (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
Several regions have different centripetal strengths compared to others. This difference means that areas with low competitiveness need to be supported by regions with strong centripetal forces in order to develop. South Lampung Regency plays a very important role in the economic, social, and political development at the regional level. Along with population growth and social changes, this regency has experienced significant development in recent years. It is necessary to identify the Regional Center System in South Lampung Regency that aligns with these recent significant developments. This research aims to understand the regional center system in South Lampung Regency. The study uses a quantitative research method, combining several analyses, including Service Index, Guttman Scalogram analysis, Marshal's Centrality Index analysis, and Rank Size Population analysis, using secondary data collection techniques. The results of the study indicate that the service centers of South Lampung Regency are located in three subdistricts: Kalianda, Natar, and Jatiagung. This is because Kalianda is the capital of South Lampung Regency, while Natar and Jatiagung are designated as Rapid Growth Strategic Areas.